Clinical outcomes and prognostic factors of head and neck squamous cell carcinoma: a ten-year follow-up study - Kelly Bienk DIAS; Laura Campos HILDEBRAND; Ana Luísa Homem de CARVALHO; Camila Alves FERRI; Jacques Eduardo NÖR; Carlos Thadeu Schmidt CERSKI; Fernanda VISIOLI; Márcia Gaiger OLIVEIRA; Pantelis Varvaki RADOS (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract Traditional guidelines for determining the prognosis of patients with head and neck squamous cell carcinoma (HNSCC) are used to make therapeutic decisions. However, only 50% of the patients had lived for more than five years. The present study aimed to analyze the correlation of traditional prognostic factors such as tumor size, histological grading, regional metastases, and treatment with the survival of patients with HNSCC. A total of 78 patients diagnosed with HNSCC were followed up for 10 years after diagnosis and treatment. The health status of the patients was tracked at four time points, and according to the evolution of the patients and their final clinical status, we performed a prognostic analysis based on the clinical outcomes observed during the follow-up period. The final study cohort comprised 50 patients. Most patients had tumors < 4 cm in size (64%) and no regional metastases (64%); no patients had distant metastases at the time of diagnosis. Most individuals had tumors with good (48%) and moderate (46%) degrees of malignancy. At the end of the follow-up period, only 14% of the patients were discharged, 42% died of the tumor, and 44% remained under observation owing to the presence of a potentially malignant disorder, relapse, or metastases. This analysis showed that traditional prognostic factors were not accurate in detecting subclinical changes or predicting the clinical evolution of patients.